RAIDD mutations underlie the pathogenesis of thin lissencephaly (TLIS). - Hyun Ji Ha; Hyun Ho Park (PLoS ONE, 2018)
Abnormal regulation of caspase-2-mediated neuronal cell death causes neurodegenerative diseases and defective brain development. PIDDosome is caspase-2 activating complex composed of PIDD, RAIDD, and caspase-2. Recent whole-exome sequencing study showed that the RAIDD mutations in the death domain (DD), including G128R, F164C, R170C, and R170H mutations, cause thin lissencephaly (TLIS) by reducing caspase-2-mediated neuronal apoptosis. Given that the molecular structure of the RAIDD DD:PIDD DD complex is available, in this study, we analyzed the molecular mechanisms underlying TLIS caused by the RAIDD TLIS variants by performing mutagenesis and biochemical assays.